Theological Insight into the Phenomenon of Life: the Bios as a Vestigium Dei - Duszek, Kamil (Teologia w Polsce, 2020)
Contemporary discussion on the phenomenon of life is a meeting point for natural sciences and religion. In their dialogue, two extreme opinions prevail, which make us understand life either as a coincidental product of evolution or as an intelligent design created by an external intervention. Both views are reductionist and represent a misunderstanding of the multi-planar character of human cognition. Mature theological insight should not follow this path. Therefore, the article is an attempt to look at the phenomenon of life in a different way. It takes up the theological interpretation of biological life, according to the medieval-originating category of vestigium Dei. However, this notion must be reconstructed in such a way that it takes into account the semantic matrix that developed around it in the twentieth century. The newly developed category of vestigium is a hermeneutical key that allows us to better understand what it means that life, already in its basic manifestations, has a transcendental reference to God, as His trace.